Analisis Penerapan Sistem Informasi Akuntansi Dalam Menunjang Efektivitas Pengendalian Internal di PUSKUD Riau - Afriani Suriati (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The aim of this research is to apply knowledge of accounting information system analysis in supporting the effectiveness of internal control at PUSKUD Riau. This research was conducted from October 2023 – January 2024. This research was conducted to find steps or recommendations for problems found in supporting the effectiveness of internal control. This type of research is descriptive qualitative, and the type of data used is secondary data obtained from the financial report of PUSKUD Riau and primary data through interviews with operational managers, accounting and marketing staff of PUSKUD Riau. The data analysis technique used in this research is data reduction, comparing theory and practice and drawing conclusions. Based on the research results, it can be concluded that the accounting information system implemented by PUSKUD Riau in the cash and credit sales system is quite good, but internal control is still less effective.